Development of a nitric oxide measurement method in tissue media - Bishop, Cherelle M., author; Reynolds, Melissa, advisor; Henry, Charles, committee member; Tobet, Stuart, committee member (Colorado State University. Libraries, 2012)
Nitric oxide (NO) is involved in many biological pathways such as vasodilatation and cellular migration. The biological roles of NO have been most heavily investigated using cell and tissue culture models. The limitations with current analytical measurement methods used most commonly with these studies, however, are that they often do not record in real-time or measure NO directly. This makes it difficult to understand the concentration dependent response activity of NO. To overcome these limitations, a measurement method has been developed that enables the real-time measurement of NO in buffered tissue media (pH 7.4, buffered with CO2 gas, 37 °C). The design of our system included multi-volume custom sample cells with a pH probe and multiple gas supply inputs, a flow regulated CO2 gas system and a chemiluminescence detector. Results demonstrated the expected first-order NO release kinetics using a model NO donor (MAHMA/NO) in phosphate buffered saline (PBS) over a specified volume range. The following half-lives were found: 63±2 s (2 mL), 65±2 s (6 mL), 63±4 s (8 mL) and 67±9 s (10 mL). Using this method at these buffer volumes, an experiment was conducted using 11 mM MAHMA/NO stock used to demonstrate that NO release was linearly proportional with respect to buffer volume with a linear fit of R2 =0.9936. The linearity of NO release allowed NO release measurements of 4.4 x 10-7 M MAHMA/NO concentration in 10 mL PBS achieving NO recovery of 117±2 and MAHMA/NO decomposition half-lives 66±2. The analysis of a 10-7 M MAHMA/NO was not measurable previously using other chemiluminescence methods. Subsequent results in tissue media buffered with 5% CO2 at a controlled rate of 20 mL/min showed statistically similar kinetic rates 68±5 s (2 mL) to that of the PBS, demonstrating the ability to measure NO in real time under tissue conditions. The simultaneous pH measurements confirmed that the pH was constant at 7.4 during the NO release portion of the experiment, an important aspect to maintain accurate kinetics. Using this method for NO release measurement in tissue media, another NO donor, DETA/NO, was used to look at steady-state release for 1.5 h. The total NO release was 0.12±0.02 (nmol) and the NO release rate was 22±3 (fmol/s). This is the first analytical measurement method that enables detection of NO release from NO donors in buffered tissue media method mimicking in vitro condition.
Keywords: nitric oxide; multi-volume studies; MAHMA/NO; diazeniumdiolates; chemiluminescence; tissue media